Os Silenos de Alcibíades de Erasmo de Rotterdam - Gonçalves, Handley Alves (2014)
The intent of this work is checking the thought of Erasmus of Rotterdam, starting from one of his adages, Silenus of Alcibiades. This adage will find a true sense in Antibarbari, explaining the need to return to Studias Humanitatis. The sense of true Silenus would be the matching between what was professed by lips and the acquired content from the study of the classics. Erasmus will show us that, in fact, the religious, like the Apostles, should have and they had a profane erudition.